By-elections in Myanmar : too early to lift sanctions - Alex Bookbinder (2012)
The victories by Aung San Suu Kyi and her party in recent by-elections in Myanmar signal a step forward in its political reform. Removing Western sanctions now would give Naypyidaw no further incentive to continue the reform process.